Current Trends in Diffusion Bonding of a Titanium Alloy to a Stainless Steel with an Aluminium Alloy Interlayer - K. Chandrappa; Amit Kumar; Kumar Shubham (Advanced Aspects of Engineering Research Vol. 4, 2021)
Diffusion bonding is the process of joining similar or dissimilar materials at the interface rather than edge joining using welding process or other metal joining processes. It is a solid state welding process carried out under the conditions of soaking temperature, bonding time and load on the surfaces to be joined. Generally this is carried out under vacuum or inert atmosphere to avoid interface reactions to actuate the corrosion. The diffusion bonding process is a means of transferring atoms from one surface to another and breaking of aspirates on the surfaces of bonding or diff using of clusters of atoms of the similar and dissimilar metals. Diffusion bonding process done at different conditions of temperature, bonding time and load. These parameters are optimised for better bond strength, the bonded specimens are analysed for micro structural changes and bond strength since diffusion bonding is an atomic transfer between the surfaces. The micro hardness test is conducted to evaluate the bond strength at the interface. The strength of the bond can be improved by inserting another material at the interface as an interlayer. The base metal titanium with stainless steel is bonded with aluminium as an interlayer.